Analisis Anteseden Semangat Kerja Pada Karyawan UMKM Hijab di Desa Bolo Kecamatan Demak - Aulia, Ananda Rahma; Efriyani Sumastuti, Efriyani Sumastuti; Setyorini, Noni (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This research aims to analyze the influence of work environment variables, work stress, work conflict, organizational communication and leadership style on the work spirit of Hijab MSME employees in Bolo Village. The population in this study was 190 employees; the sample determined in this study was 128 employees using a saturated sample. In this research, a sampling technique was carried out by distributing questionnaires.. The findings of this research are that the work environment has a positive and significant effect on the work morale of Hijab MSME employees in Bolo Village, work stress has a positive and significant effect on the work spirit of Hijab MSME employees in Bolo Village, work conflict has a positive and significant effect on the work spirit of Hijab MSME employees in the Village. Bolo, organizational communication has a positive and significant influence on the work morale of Hijab MSME employees in Bolo Village, and leadership style has a positive and significant influence on the work spirit of Hijab MSME employees in Bolo Village.